Rituximab Monotherapy for Primary Cutaneous Follicle Center Lymphoma - Dhakal, Ajay; Tretheway, David M; Fulton, Rebecca; Shah, Binay Kumar (Journal of Advances in Internal Medicine, 2012)
Primary cutaneous follicle center lymphoma is a rare disorder. Although there are several treatment options, large clinical trials on the treatment of primary cutaneous follicle center lymphoma are lacking. Optimal treatment of this disease is unclear. We describe a case of primary cutaneous follicle center lymphoma treated with systemic rituximab, and review the literature. DOI: http://dx.doi.org/10.3126/jaim.v1i1.5834 Journal of Advances in Internal Medicine. 2012; 1(1): 16-18